Cloud system scaling for NetApp - Róslín Erla Tómasdóttir 2000-; Svanhildur Einarsdóttir 2000- (2022)
Cloud services are becoming an increasingly popular method for storing data. Cloud services give users, and companies access to services and data through the internet in an affordable manner without needing access to any hardware or other infrastructure. This project was done in cooperation with NetApp Iceland, which is a subsidiary of NetApp Inc. in the United States and specialises in cloud solutions. The Cloud Volume Service (CVS) is the core backend component responsible for processing user requests for the companies’ cloud services, so it can be thought of as a connection between their clients and their cloud. The system was running into problems regarding deadlocks and slow response time, in most cases, while processing long-running operations such as object creation. To solve this problem, the system was split into smaller components to distribute and schedule its request load. A cache was created and used for validation purposes to lessen the load on the database. With this optimisation, the main goal of improving system performance was fulfilled. The particular request modified in the project had time improvements on the local environment for all cases, and the load on the database was reduced.